Burning of the marriage hat : a novel of high plains women - Benshoof-Holler, Margaret (San Francisco, California : Wind Women Press, 2002)
Just as the Wyoming wind carries small tinge of my grandmother's voice as it blows across the prairie, it reminds me that I found no comfort out here on the high plains after my daughter was born and taken away. It was as if she had died. But, there was no funeral. I wore no mourning shroud. Nowailing wall for me to go to pound my fists and cry to the gods! "Carmen! Carmen!
Includes bibliographical references.
Keywords: Unmarried mothers -- Fiction; Domestic fiction